I Deserve More! An Experimental Analysis of Illusory Ownership in Dictator Games - Kandul, Serhiy; Nikolaychuk, Olexandr (My University, 2018)
Delineation of someone's ownership typically involves the sense of deservedness: the property right is respected as long as the owner deserve to own the object. Objectively, deservedness is often linked to one's actions or specific attributes that justify the owner's claims. We argue that people might get the sense of deservedness without an objective causal attribution. In our experiment, the pure luck defines the allocation of the roles. Still, compared to a standard setting, in a treatment where actions have no causal effect on the outcome, dictators keep larger share. At the same time, dictators do not compensate recipients for their irrelevant actions. We interpret this asymmetry in reaction towards the procedures of role allocation as 'illusory property': people care about irrelevant procedures only if they favor themselves but not others.